I used to work at Goldman Sachs! How firms benefit from organizational status in the market for human capital. (16th May 2014) - Bidwell, Matthew; Won, Shinjae; Barbulescu, Roxana; Mollick, Ethan
<x xml:space="preserve">Abstract</x> How does employer status benefit firms in the market for general human capital? On the one hand, high status employers are better able to attract workers, who value the signal of ability that employment at those firms provides. On the other hand, that same signal can help workers bid up wages and capture the value of employers' status. Exploring this tension, we argue that high status firms are able to hire higher ability workers than other firms, and do not need to pay them the full value of their ability early in the career, but must raise wages more rapidly than other firms as those workers accrue experience. We test our arguments using unique survey data on careers in investment banking. Copyright © 2014 John Wiley & Sons, Ltd.